Treatment of metastatic squamous cell carcinoma arising in sacrococcygeal pilonidal sinus: a case report series - Soria Rivas, Ainara; Bea-Ardebol, Sonia; Vida Navas, Elena; Muñoz-Arrones, Óscar M.; Cabañas-Montero, Luis Jacobo; Mena-Mateos, Antonio; López-Campos, Fernando; Corral Moreno, Sara; Pérez-Muñoz, Israel; González Lizan, Fausto; Sanz Pascual, María; Serrano Domingo, Juan Jose (Frontiers in Medicine, 2023)
Cutaneous squamous cell carcinoma arising in a pilonidal sinus is a very rare entity, with an estimated 100 cases reported in the literature, the vast majority of which are localized. Metastatic disease or disease that requires systemic treatment is even rarer, which represent a therapeutic challenge. In this sense, we aim to share our experience as multidisciplinary team in the treatment of this entity, at the same time that we try to summarize the evidence published to date. To the best of our knowledge, this is the largest series published to